Пошаговое объяснение:
1) ((1-x^2)^(-2))` = -2/(1-x^2)^3 * (-2x) = 4x / (1-x^2)^3
2) 4*sin*x * cosx - 7 * cosx = 2*sin(2x) - 7*cosx
3) 2*cos(2x)*cos(3x) - 3*sin(2x)*sin(3x)
4) y ' = lnx-1 + x*1/x = lnx
5) (e^x*2^x - e^x * 2^x * ln2) / 2^(2x) = (e/2)^x *(1 - ln(2)) = (e/2)^x * ln(e/2)
6) 1 / ((sin(2x))^2) * 2*sin(2x) * cos(2x) * 2 = (4*sin(2x)*cos(2x)) / ((sin(2x))^2) = 4*cos(2x) / (sin2x) = 4*ctg(2x)
7) 5*(xe^(2x) + 3)^4 * (e^(2x) + 2*x*e^(2x)) = 5*e^(2x) * (2x+1) * (xe^(2x) + 3)^4
8) y ' = (-(sinx)^2 - (cosx)^2) / (sinx)^2 = - 1 / (sinx)^2
y() ' = - 1 / (1/)^2 = -2
9, 10) не до конца видно задания
84:2=42
100-42=58
58+18=76
38+45:(33-24)=43
33-24=9
45:9=5
38+5=43
15*3:9+12*(32-34):3=-3
15*3=45
45:9=5
32-34=-2
12*(-2)=-24
-24:3=-8
5+(-8)=5-8=-3
32*3-72+(67-59)*3=48
32*3=96
96-72=24
67-59=8
8*3=24
24+24=48